Serological survey of anti-Leptospira spp. antibodies in individuals with animal hoarding disorder and their dogs in a major city of Southern Brazil - Cunha, Graziela Ribeiro da; Pellizzaro, Maysa; Martins, Camila Marinelli; Rocha, Suzana Maria; Yamakawa, Ana Carolina [UNESP]; da Silva, Evelyn Cristine [UNESP]; dos Santos, Andrea Pires; Morikawa, Vivien Midori; Langoni, Hélio [UNESP]; Biondo, Alexander Welker (Wiley, 2022)
Background: Individuals with hoarding disorder (HD) presented a persistent difficulty in detaching from objects and/or animals. Unhealthy conditions, frequently found in cases of animal HD (AHD), may favour environmental contamination and the spread of zoonotic pathogens. Despite that, only one study of zoonotic diseases in individuals with AHD and their companion animals has been conducted to date. Objectives: This study aimed to assess the seroprevalence of anti-Leptospira spp. antibodies in individuals with AHD and their dogs in a major city of Southern Brazil. Methods: Blood samples were obtained from 264 dogs (21 households) and 19 individuals with AHD (11 households) and tested by microscopic agglutination test. Results: All human samples were seronegative. Seropositivity was found in 16/264 (6.1%; CI 95% 3.3–9.6%) dogs from 11/21 (52.38%) households, with titres ranging from 100 up to 400, and Copenhageni (10/16; 62.5%) was the most frequent serovar. Surprisingly, seropositivity of hoarded dogs found herein was among the lowest reportedly observed in other dog populations of Brazil. Two epidemiological variables were significantly associated with seropositivity in dogs: the presence of cat hoarding (p = 0.004) and the report of flood occurrence in the household (p = 0.031). Conclusions: No individuals with AHD were seropositive, and besides the lower seroprevalence of dogs, they probably had contact with Leptospira spp. at some point in their life. Since dogs can be considered potential sentinels in leptospirosis, public health programs must become aware of the risk of leptospirosis cases in households of individuals with AHD and nearby communities.
Keywords: hoarding disorder; leptospirosis; One Health; sentinel surveillance